(Liquid + liquid) equilibria for mixtures of dodecane and ethanol with alkylsulfate-based ionic liquids. (February 2015) - Mungar Ram, Niren; Naidoo, Paramespri; Letcher, Trevor M.; Ramjugernath, Deresh
Graphical abstract: Highlights: LLE data for dodecane + ethanol + 1-alkyl-imidazoluim-based ionic liquids (ILs). ILs are [Mmim][MeSO4 ], [Emim][MeSO4 ], and [Bmim][MeSO4 ]. Measurements at T = 298.15 K and 0.101 MPa, as well as at T = 313.15 K for [Mmim][MeSO4 ]. Consistency of the tie-lines checked with the Othmer–Tobias and Hand equations. Data correlated with the NRTL model. Abstract: The ternary (liquid + liquid) equilibrium (LLE) data for mixtures of dodecane (C12 H26 ) and ethanol with ionic liquids 1, 3-dimethylimidazolium methylsulfate [Mmim][MeSO4 ], 1-ethyl-3-methylimidazolium methylsulfate, [Emim][MeSO4 ] and 1-butyl-3-methylimidazolium methylsulfate, [Bmim][MeSO4 ], were studied at T = 298.15 K and 0.101 MPa. The selectivity and solute distribution coefficient ratios determined from the data were used to examine the possibility of using these ionic liquids for extraction of ethanol from dodecane. The temperature dependency was investigated by measuring the LLE data for dodecane + ethanol + [Mmim][MeSO4 ] at T = 313.15 K and 0.101 MPa. The Othmer–Tobias and Hand equations were used to test the consistency of the tie-line data. The tie-line data were correlated with the Non-Random Two Liquid (NRTL) equation which provided a good model and representation for the experimental results.